Targeted analysis of bioactive phenolic compounds and antioxidant activity of Macedonian red wines. (15th March 2015) - Ivanova-Petropulos, Violeta; Ricci, Arianna; Nedelkovski, Dusko; Dimovska, Violeta; Parpinello, Giuseppina P.; Versari, Andrea
Highlights: 19 phenolic compounds were identified and quantified in Macedonian wines. The influence of variety and yeast strains on phenolics was studied. Vranec presented highest content of phenol acids and anthocyanins. Locally isolated yeasts provided higher levels of polyphenols and antioxidant activity. Abstract: Phenolic composition of twenty-two Macedonian red wines, including ten autochthonous monovarietal Vranec wines produced with different yeasts for fermentation, and twelve wines from international varieties (Syrah, Merlot and Cabernet Sauvignon) from different wine regions was studied. All wines presented relatively high value of total phenols and antioxidant activity. A total of 19 phenolic compounds were identified and quantified using HPLC-DAD and among them, malvidin-3-glucoside and its derivatives were the major compounds, followed by the petunidin derivatives, while caftaric acid was the predominant cinnamic acid derivative in all wines. The anthocyanin content was mainly affected by the grape variety and to a less extent by the yeast used in fermentation. In particular, the use of locally isolated yeasts affected higher amount of anthocyanins and phenolic acids compared to the wines fermented with commercial yeasts. Principal Component Analysis showed a satisfactory grouping of red wines according to the grape variety.